SAFETY AND OUTCOME OF SAME DAY DISCHARGE VS OVER-NIGHT STAY AFTER ELECTIVE PCI IN PATIENTS WITH STABLE CAD: A RANDOMIZED CONTROL TRIAL IN ARMY CARDIAC CENTE - Malik, Muhammad Faheem Iqbal; Khan, Muhammad Nadir; Yusuf, Muhammad Tahir; Ahmad, Ayaz; Ahmed, Muhammad Shoaib; Danyal, Shoaib Muhammad (Pakistan Armed Forces Medical Journal, 2019)
Objective: To determine and compare the safety and outcomes of same day discharge patients with over-night stay patients after elective percutaneous coronary interventions with stable coronary artery disease.Study Design: Randomized controlled trial.Place and Duration of Study: This study was conducted at Army Cardiac Center, Lahore from, Jun 2017 to Jul 2018.Methodology: Hundred patients with stable CAD were recruited after their informed consent. Patients were randomized through lottery method using list of patients. Fifty patients were discharged on the same day of PCI while 50 patients stayed over-night. Inclusion Criteria was patients of either gender with age 30%, Serum creatinine